KINETIKA REAKSI HIDROLISA KULIT DURIAN MENJADI GLUKOSA DENGAN KALISATOR HCl PADA TANGKI BERPENGADUK (Jurnal Teknologi Pangan, 2013)
This  study  aims  to  develop  mechanisms  of  the  reaction  kinetics  of  hydrolysis  into glucose durian skin with HCl catalyst in the stirred tank, to obtain  data that is the  price reaction kinetics reaction rate constants (k) and  activatin energy. The study was condcted after the first with dry skin so that the  water content lost durian , durian skin  after  it  is  made  of  powder  and   sieved  to  pass  20  mesh  particle  size,  and  durian leather  was  put  into  a   three  neck  flask  with  100  cc  of  didtilled  water  was  added,  as  catalyst   was  added  HCl  1N  200  cc  and  the  hydrolysis  process  carried  out  in  accordance  with  the  time  and  temperatuure  have  been  determined  with  a   stirring speed of 200 rpm. After the hydrolysis the solution was neutralized by adding NaOH and  filtered  to  take  filtrate.  Filtrate  evaporated,  so  that  is  left  is  then  carried  out  an analysis  of  concentrated  glucose  levels  using  Luff  Schrool.  Variables  run  time  of hydrolysis  40;50;60;70;80  minutes  and  the  temperature  of  hydrolysis  75;80;85;90; 95°C.  From  the  results  of  this  study  found  the  greatest  conversion  is  0.072 at  95°C  and time 80 minutes, k obtained by 5,147.10-6e-1038,4710/RT . In this study the following shrinnking core model with chemical reaction as controller, and the reaction followed first order reaction.Key words: Glucose, speed of reaction, activation energy